Showcasing an Alternative Educational Systems Using the Philosophy of Ulul Albab - Rohaizan, Baru; Syed Mohd Azmi, Syed Ab. Rahman; Abdul Hakim, Abdullah (2014)
Imtiaz schools, which have become a household name and craze among parents who want to send their children there to study, has become a determining factor for a need to initiate a research to evaluate how far the founding objectives have materilized into actions and reality. Besides carrying out a research with the objective of determining the positive aspects of these schools, which have earned a name of being an integrated leaning institution, a comprehensive profile of these Imtiaz schools could be structured and propagated to all interested parties at the end of the research. Qualitative data was obtained from interviews with the school’s management, Terangganu Foundation as the authority in-charge of Imtiaz schools, general interviews and focus group discussions with teachers, students and parents in order to examine the actual implementation and achievement of all the targeted objectives. All the information gathered in this research had achieved and fullfilled the objectives of the research. The research found that the student’s and teacher’s understanding and appreciation towards the school’s mission and vision was clear. The concept of virtuousity (a.k.a the Ulul Albab Concept) which has been vociferated and hailed, has been acknowledged by students and teachers of its existence and has been transformed into the lessons, learning and all the activities that have been planned and implemented. The process of assessing students, co-curriculum activities and involvement with the community has become the catalyst to the success and achievement of the targeted objectives.